Theoretical reflections of Leininger's cross-cultural care in the context of Covid-19 - Graziela Maria Ferraz de Almeida; Tayomara Ferreira Nascimento; Rosemary Pereira Lino da Silva; Marielle Poyo Bello; Cassiana Mendes Bertoncello Fontes (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To reflect on cross-cultural care for the population based on the theoretical assumptions and concepts of Leininger's Transcultural Theory, related to the recommendations for combating the Covid-19 pandemic. Method Reflective theoretical study based on culturally competent care, related to the Brazilian reality, using the conceptual attributes of care, culture, and worldview. Critically articulated the reasonings about the guidelines for preserving, accommodating, and repatterning actions for the care of people. Results The nurse must know cross-cultural care in order to consider individual and/or collective treatment and respect the existing differences in beliefs and values. This premise corroborates the adherence to Covid-19 prevention and treatment recommendations. The lack of knowledge about the transmissibility and invisibility of the virus and the risk factors, combined with the cultural diversity of the population, can make it difficult to adhere to health recommendations. Final considerations Cross-cultural care favors the practice of health education and can provide conditions for greater adherence of the population to nursing actions.